Analysis of Conceptual Metaphors in Deutschewelle Newspaper based on the Perspective of Linguistic Relativity - Novia Anjani Dewi (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2021)
Generally, metaphor is a language style that is often used as a form of creativity in communicating. However, the wider scope of the use of metaphors has led to interference from other aspects, one of which is the cultural aspect. Cultural aspect is considered to play an important role in shaping the way each individual perceives something. To prove this perspective, this study aims to identify whether the use of metaphors can be influenced by culture, when compared to the perspective of linguistic relativity. The object of this research was discourse text in Deutchewelle newspapers in Indonesian and German. The 5-Step Metaphor Analysis Method was used in this research. From the results of the meaning analysis that has been done, it shows that there is a conceptual metaphor use which is influenced by cultural aspect. This means that the use of metaphors based on the perspective of linguistic realativity is acceptable.